Changing Features of Hallyu in Vietnam and Ways of Cooperation for Cultural Development - Lee Han Woo; Nguyen Thi Thanh Huyen, (Tạp chí Khoa học Xã hội và Nhân văn (VNU Journal of Social Sciences and Humanities), 2025)
Since the official establishment of Vietnam – South Korea diplomatic relations in December 1992, the exchange and cooperation in the field of culture have also been expanding. One of the essential marks is the introduction and spread of the Korean Wave (Hallyu) in Vietnam. This article documents the transformation of Hallyu in Vietnam in the mid-2000s from television drama series to K-pop. It then summarises the changes in Hallyu's reception among the Vietnamese public simultaneously. Finally, the article suggests some prospects for bilateral cooperation in the field of culture in general by studying the achieved results of cultural exchanges between the two countries. Based on the demands and capabilities of both countries' cultural sectors, this article proposes a plan to promote further cooperation in the field of culture between the two countries. The article uses analytical methods to synthesize materials from books, newspapers, blogs, and surveys on the cultural exchanges between Vietnam and South Korea. It also utilizes the opinions of both countries' experts on the cultural interaction between two countries related to the subject matter.Received 12th August 2022; Revised 2nd September 2022; Accepted 10th October 2022